Egg quality characteristics of three strains of layer chickens, a principal component analysis - Udeh, I.; Akporhuarho, O. P.; Matthew, E. F. (Diponegoro University, 2022)
The aim of this study was to compare the external and internal egg quality of three layer strains namely Bovan Nera, ISA Brown and FUNAAB Alpha. One hundred and fifty eggs sampled from 120 birds per strain from 35 to 45 weeks of age were used for the study. Data collected were analysed using one way analysis of variance in a completely randomized design. ISA Brown had significantly (P<0.01) the heaviest eggs on the average at 45 weeks, followed by Bovan Nera and FUNAAB Alpha. The egg quality characteristics of Bovan Nera and ISA Brown were similar but significantly (P<0.05) superior to FUNAAB Alpha in egg width, egg volume, egg surface area and albumen weight. FUNAAB Alpha was significantly (P<0.05) the most superior in yolk weight only. Three principal components (PC1, PC2 and PC3) were produced from each strain after principal component analysis and varimax rotation. Estimation of breeding values based on the three principal components could be used for the selection and improvement of egg quality variables in each strain instead of isolated traits.